Development of a surgical guide using open-source software for a dental implant placement - Mayasari, Dita Ayu; Kurniatie, Menik Dwi; Prasetyanto, Wisnu Adi; Fadhila, Shafa Salsa; Wicaksono, Bonifasius Primario; Hendrawan, Reza Dony (Majalah Kedokteran Gigi Indonesia, 2025)
Dental technology has advanced significantly in recent years, particularly with regard to the placement of dental implants to replace lost teeth. One such technology is the use of a dental implant guide as a tool to assist with implant installation. The primary purpose of a dental implant guide is to assist the dentist in placing implants with accuracy and precision to maximize operation success and minimize risk of problems. Dental implant guides customized to each patient’s unique tooth and jaw architecture are made possible in large part by digital dentistry. To ensure that the implant is positioned optimally in relation to the patient’s teeth and jaw anatomy, customization is important. Using the AutoDesk meshmixer for modeling and manufacturing, a 3D slicer to segment the mandible using a 3D segmentation approach and 3D printing using resin and filament are all part of the dental implant guide design process. To improve precision and customization in the placement of dental implants, this comprehensive strategy makes use of digital dentistry.